Pola Komunikasi Politik: Studi Pilkada Gubernur Gorontalo - Erwin Jusuf Thaib; Abdul Razak Mozin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This study is about to reveal how political communication of Golkar Party actors in Gorontalo Governor Election of 2011. The results of this study indicate that the strength of Golkar's political communication performance in Gorontalo Governor Election in 2011 is on party communicators and actors. Where the model of political communication occurs at several levels, namely; (a) the individual level, Rusli Habibie-Idris Rahim managed to manage the impression in each of them well. (b). At the group level, it is clear how Rusli Habibie-Idris Rahim managed to manage his political communications with harmonization in policy sharing and political talks. (c) at the organizational level impacted further from the group level, ie how Golkar and PPP determine the political direction of the party that position itself as the defender of the people; and (d) At the mass level, the Golkar Party is melting in coalition partners with the PPP, so the Gorontalo public sees any positive value from Golkar and PPP. Golkar and PPP always get a positive score. This is because Rusli Habibie-Idris Rahim always advances as a public policy advocate.